Snow thermal state monitoring at the observation site of Lomonosov Moscow State University (MSU) in 2024 - Frolov D.M.; Gagarin V.E.; Koshurnikov A.V.; Rzhanitsyn G.A.; Sidorova T.A. (BIO Web of Conferences)
The 2023 climate report suggests that there may be rising greenhouse gas levels, record global temperatures and significant glacier melt. The summer of 2024 saw some of the highest temperatures on record in the Northern Hemisphere, with Moscow experiencing its warmest September in 150 years and an unusually dry climate. Snow observations at MSU involve analysing a number of factors related to snow cover dynamics, including snowfall types, accumulation, and melting processes. Research also encompasses measuring snow density and structure, accommodating uneven terrain, and understanding weather influences on snow and ground thermal state and heat transfer properties. The findings contribute to our collective understanding of the cryosphere's evolution amidst climate change.